2012
DOI: 10.1111/j.1742-4658.2012.08723.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and chitin oligosaccharide‐binding mode of a ‘loopful’ family GH19 chitinase from rye, Secale cereale, seeds

Abstract: The substrate-binding mode of a 26-kDa GH19 chitinase from rye, Secale cereale, seeds (RSC-c) was investigated by crystallography, sitedirected mutagenesis and NMR spectroscopy. The crystal structure of RSC-c in a complex with an N-acetylglucosamine tetramer, (GlcNAc) 4 , was successfully solved, and revealed the binding mode of the tetramer to be an aglycon-binding site, subsites +1, +2, +3, and +4. These are the first crystallographic data showing the oligosaccharide-binding mode of a family GH19 chitinase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 37 publications
(101 reference statements)
2
30
0
1
Order By: Relevance
“…The mode of (GlcNAc) 4 binding to subsites +1 to +4 was partly similar to that observed in the crystal structure reported for RSC-c liganded with (GlcNAc) 4 [18]; however, some interactions were rearranged in RSC-c-E67Q/W72A liganded with 2 Â (GlcNAc) 4 , as shown in Fig. 3.…”
Section: (Glcnac) 4 Binding Mode To Subsites +1 To +4supporting
confidence: 84%
See 1 more Smart Citation
“…The mode of (GlcNAc) 4 binding to subsites +1 to +4 was partly similar to that observed in the crystal structure reported for RSC-c liganded with (GlcNAc) 4 [18]; however, some interactions were rearranged in RSC-c-E67Q/W72A liganded with 2 Â (GlcNAc) 4 , as shown in Fig. 3.…”
Section: (Glcnac) 4 Binding Mode To Subsites +1 To +4supporting
confidence: 84%
“…We compared the main chain conformation of RSC-c-E67Q/ W72A liganded with 2 Â (GlcNAc) 4 to those of unliganded RSC-c (PDB code: 4DWX) and RSC-c liganded with (GlcNAc) 4 (PDB code: 4DYG), in which only one (GlcNAc) 4 molecule bound to subsites +1 to +4 [18]. As shown in Fig.…”
Section: Overall Structure Of Liganded Rsc-c-e67q/w72amentioning
confidence: 99%
“…Structural alignment of loop III, including 20 residues in each end, demonstrated that even though CatD1 was crystallized in the absence of ligands the loop III is in a closer conformation to the one present in the rye structure with bound ligands in the groove [40] (Fig. 5D) (rmsd 0.69 A), while the rmsd is 1.0 A when compared with the structure of the rye chitinase without ligand [39]. Loops IV and V showed similar displacements (Fig.…”
Section: Overall Structure Of the Hbclp1 Domainsmentioning
confidence: 99%
“…Recently, the crystal structure of a class IV chitinase from corn (Zea mays) that lacks the CBD provided evidence of the participation of residues Gln62, Arg177 and Glu165 in chitin hydrolysis and of Ser103 and Tyr106 in substrate binding; however, class IV chitinases have evolved to accommodate shorter substrates [42]. Compared with the chitinases of classes I, II and IV [39,[41][42][43], our CatDs exhibit all of the residues that have been implicated in catalysis, thereby allowing our mutants HbCLP1-A117E and HbCLP2-A147E to recover their chitinolytic activity.…”
Section: Chitinase Activitymentioning
confidence: 99%
See 1 more Smart Citation